BIOSINTESA FOLAT OLEH BAKTERI ASAM LAKTAT - Purwandhani, Siti Nur (Universitas Widya Mataram, 2016)
Folate, an important B-group vitamin, participates in many metabolic pathways such as DNA and RNA biosynthesis and amino acid inter-conversions. Mammalian cells cannot synthesize folate; therefore, an exogenous supply of this vitamin is necessary to prevent nutritional deficiency. Folic acid is a composite molecule, being made up of three parts: a pteridine ring system (6-methylpterin), para-aminobenzoic acid , and glutamic acid . The folate biosynthesis pathway in micro-organisms can be divided in several parts. The pteridine proportion of folate is made from GTP, that is synthesized in the purine biosynthesis pathway. p-Aminobenzoic acid originates from chorismate and can be synthesized via the same biosynthesis pathways required for the aromatic amino acids, involving glycolysis, pentose phosphate pathway and shikimate pathway. The third component of a folate molecule is glutamate, that is normally taken up from the medium. This review will focus on biosynthesis and folate production by lactic acid bacteria and the folate level production in fermented product.